2011
DOI: 10.3109/17435390.2011.572195
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of cellular adaptation to quantum dots – the role of glutathione and transcription factor EB

Abstract: Cellular adaptation is the dynamic response of a cell to adverse changes in its intra/extra cellular environment. The aims of this study were to investigate the role of: (i) the glutathione antioxidant system, and (ii) the transcription factor EB (TFEB), a newly revealed master regulator of lysosome biogenesis, in cellular adaptation to nanoparticle-induced oxidative stress. Intracellular concentrations of glutathione species and activation of TFEB were assessed in rat pheochromocytoma (PC12) cells following t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 62 publications
0
33
0
Order By: Relevance
“…This type of enlargement is a commonly reported phenomenon and has been described for various NMs including ZnO NPs, fullerenol NPs, polystyrene NPs and QDs. [27,[60][61][62] Interestingly, the increase in In combination with the reduced oxidative stress, this could explain the lack of toxicity we observed upon exposure of HeLa cells to these QDs. Our findings thus confirm that MPA-coated QDs are quite biocompatible.…”
Section: Mpa Coated Qdsmentioning
confidence: 84%
See 1 more Smart Citation
“…This type of enlargement is a commonly reported phenomenon and has been described for various NMs including ZnO NPs, fullerenol NPs, polystyrene NPs and QDs. [27,[60][61][62] Interestingly, the increase in In combination with the reduced oxidative stress, this could explain the lack of toxicity we observed upon exposure of HeLa cells to these QDs. Our findings thus confirm that MPA-coated QDs are quite biocompatible.…”
Section: Mpa Coated Qdsmentioning
confidence: 84%
“…[26] In line with the latter view, it has been suggested that the induction of autophagy could be beneficial, as the overall toxicity of NMs could be reduced by the protective effects of autophagy. [27,28] Considering the impact of autophagy induction and inhibition as described above, we believe it is critical to characterize the influence of NMs on autophagy from a nanotoxicological point of view. [18] However, despite abundant reports on NM-modulated autophagy, only a few studies exist related to QDs.…”
Section: Introductionmentioning
confidence: 99%
“…17 In addition, the transcription factor EB (TFEB) is a master regulator of lysosome and autophagy gene network, which could be activated by nanoparticle internalization. 47,48 As reported, polystyrene nanoparticles could not only upregulate TFEB transcription but also cause lysosomal dysfunction and blockage of autophagic flux. 49 Therefore, TFEB might also be involved in SiNP-induced autophagy dysfunction.…”
mentioning
confidence: 78%
“…10). Quantum dot toxicity, however, is of concern [87,88,89,90]. Cadmium selenide quantum dots are lethal to cells under UV irradiation and when their protective coating is lost intracellularly.…”
Section: Selected Therapeutic Conceptsmentioning
confidence: 99%